Rituals and routines: A joint approach to the rebellious life of teams in organizational stability and change. Issue 1 (11th February 2019) - Jouxtel, Pascal
Abstract : Purpose: The terms rituals and routines are often conflated in everyday speech about teams, which betrays a common ontology. Yet these concepts have long been researched in two segregated currents of thought: one stemming from sociology and anthropology, focused on the quality of togetherness and the other from evolutionary economics, focused on market performance. The common ontology is nevertheless present in the processual nature of rituals and routines, the underlying shared reference to the "structure-action-artifact" triad and the statement that both are sources of change as well as stability. This paper aims to assess the pertinence of a joint approach. Design/methodology/approach: The paper presents a historical and contrasted view on the two concepts. A comprehensive field observation of two teams in mid-term organizational change contexts, focused on collective "doings", is reported. The tentative "binocular lens" was made of two chosen sets of variables, drawn from the theoretical fields of rituals and organizational routines. Findings: The distinction between rituals and routines in people's perception, though largely confused, nonetheless reveals the tension between variable and opposing demands for both change and stability from the team side and from the organization side. Their joint action is effective in enhancing the team's feelings of confidence and control over its own performance and its future within the organization. Research limitations/implications: This paper is supported by a comparison of only two teams, leaving room for further empirical research about the effects of endogenous rituality and localized routines on autonomy, efficiency and pride. Originality/value: This paper offers a new theoretical joint view on the two concepts and explores an endogenous potential for organizational change feeding on emotional and symbolic aspects of team work.